Clinical measurement of maximum mouth opening and its relation to different facial types in children of Saudi Arabia - Asiri, Shmookh Abdullah Alhayani; Togoo, Rafi Ahmad; Al Gelban, Lamis Omer Saad; Almathami, Shouq Abdulrahman; Alabsi, Rehab Abdulwahab M; Tariq, Rema Misfer; Ain, Tasneem Sakinatul (Vojnosanitetski pregled, 2023)
Background/Aim. The decreased mouth opening (MO) is a key factor in diagnosing most oral health-related issues. The aim of the study was to assess the magnitude of the maximum mouth opening (MMO) and its correlation with the facial types of children in the southern part of Saudi Arabia. Methods. A cross-sectional study was conducted in a group of 555 children ranging from 2 to 12 years of age. The MMO was measured as the distance between the incisal edge of maxillary and mandibular central incisors in the midline using the digital Vernier caliper. Three readings of MMO value were obtained, and the average mean of these readings was taken as the final MMO value. Based on the calculated facial index (FI), five facial types were determined in the study subjects: hypereuryprosopic (very broad face, FI range ≤ 79.9); euryprosopic (broad face, FI range 80–84.9); mesoprosopic (round face, FI range 85–89.9); leptoprosopic (long face, FI range 90–94.9); hyperleptoprosopic (very long face, FI range ≥ 95). Subjects were categorized and compared accordingly. The facial profile, height, weight, and body mass index (BMI) of each subject were recorded as well. The data hence obtained was subjected to statistical analysis using SPSS (version 19.0, SPSS Incorporated, Chicago, IL, USA). Results. The overall mean value ± standard deviation of MMO for all the subjects in the study was 47.3 ± 8.7 mm. The mean value of MMO in hyperleptoprosopic children (FI range ≥ 95.0) was significantly higher than in other children. The mean difference value of MO in mesoprosopic (FI range 85.0–89.9) children was significantly lower than in leptoprosopic (FI range 90.0–94.9) and hyperleptoprosopic (FI range ≥ 95.0) children. The mean difference value of MO of the leptoprosopic (FI range 90.0–94.9) type was significantly lower than that of the hyperleptoprosopic type (FI range ≥ 95.0). Conclusion. Based on the analyzed results, it was found that the MMO correlates with different facial types and facial profiles among the studied population.
Keywords: anatomy; correlation of data; dental care for children; face; orthodontics; saudi arabia